Cost‐effectiveness of secukinumab as first biologic treatment, compared with other biologics, for moderate to severe psoriasis in Germany. (27th June 2018) - Augustin, M.; McBride, D.; Gilloteau, I.; O'Neill, C.; Neidhardt, K.; Graham, C. N.
Abstract: Background: Secukinumab, a fully human monoclonal antibody that selectively neutralizes interleukin 17A, has demonstrated strong and sustained efficacy in adults with moderate to severe psoriasis in clinical trials. Objective: This analysis compared the cost per responder of secukinumab as first biologic treatment of moderate to severe psoriasis, with adalimumab, infliximab, etanercept and ustekinumab in Germany. Methods: A 52‐week decision‐tree model was developed. Response to treatment was assessed based on the likelihood of achieving a predefined Psoriasis Area and Severity Index (PASI) response to separate the cohort into responders (PASI ≥75), partial responders (PASI 50 to 74) and non‐responders (PASI <50). Responders at week 16 continued initial treatment, whereas partial responders and non‐responders were switched to standard of care, which included methotrexate, cyclosporine, phototherapy and topical corticosteroids. Sustained response was defined as 16‐week response maintained at week 52. A German healthcare system perspective was adopted. Clinical efficacy data were obtained from a mixed‐treatment comparison; 2016 resource unit costs from national sources; and adverse events and discontinuation rates from the literature. We calculated cost per PASI 90 responder over week 16 and week 52, as well as cost per sustained responder between weeks 16 and 52. Results: Secukinumab had the lowest cost per PASI 90 responder over 16 weeks (€18 026) compared with ustekinumab (€18 080), adalimumab (€23 499), infliximab (€29 599) and etanercept (€34 037). Over 52 weeks, costs per PASI 90 responder ranged from €42 409 (secukinumab) to €70 363 (etanercept). Likewise, secukinumab had the lowest cost per sustained 52‐week PASI 90 responder (€22 690) compared with other biologic treatments. Sensitivity analyses, excluding patient copayments, showed similar results. Conclusions: First biologic treatment with secukinumab for moderate to severe psoriasis is cost‐effective, with lowest cost per responder compared with other biologic treatments in Germany.